Simulations for Flow-Symmetry Through r.avaflow in the General Two-Phase Mass Flow Model - Kafle, Jeevan; Kattel, Parameshwari (Journal of Nepal Mathematical Society, 2019)
Gravitational flows, e.g., landslide, debris flow and avalanches are hazardous mass wasting processes. The proper understanding of their dynamics is very important. As laboratory experiments can not perfectly model their initiation process and field assess of the live events are very difficult, numerical experiments have become the promising way for the study of their flow dynamics. Here we employ the enhanced version of two-phase mass flow model [33] through the open source computational code, r.avaflow to analyze the issue of symmetry in the flow. Two-phase debris mass are triggered from all the flanks of the three different pyramids (triangle-based, square-based and octagon-based) with different rotational symmetry and study the flow pattern along with maximum kinetic energy of the flow. Flow past two different types of obstacles (a tetrahedron and a square based pyramid) are also observed. The possible causes of asymmetry in the flow are also analyzed.